Neonatal and pediatric clinical pharmacology - Van den Anker, John N.; Coppes, Max J. (Max Johan); Koren, Gideon, 1947- (Philadelphia, Pa. ; Saunders, 2012)
Focuses on both general and specific aspects of neonatal and pediatric clinical pharmacology including ethics, pharmacogenomics, metabolomics, adverse drug reactions, pain medication, pulmonary hypertension and several other hot topics.
Pediatric pharmacokinetics: human development and drug disposition / Ryan S. Funk, Jacob T. Brown, and Susan M. Abdel-Rahman -- Pediatric pharmacogenomics: a systematic assessment of ontogeny and genetic variation to guide the design of statin studies in children / Jonathan Wagner and J. Steven Leeder -- Metabolomics in the developing human being / Aggeliki Syggelou ... [et al.] -- Emerging biomarkers of intrauterine neonatal and pediatric exposures to xenobiotics / Kaitlyn Delano and Gideon Koren -- New ways to detect adverse drug reactions in pediatrics / Michael Rieder -- Pharmacotherapy of pediatric HIV infection / Natella Rakhmanina and B. Ryan Phelps -- How to optimize the evaluation and use of antibiotics in neonates / Evelyne Jacqz-Aigrain, Florentia Kaguelidou, and John N. van den Anker -- Pharmacotherapy for pulmonary hypertension / Robin H. Steinhorn -- Pharmacologic management of the opioid neonatal abstinence syndrome / Walter K. Kraft and John N. van den Anker -- Update on pain assessment in sick neonates and infants / Monique van Dijk and Dick Tibboel -- The impact of extracorporeal life support and hypothermia on drug disposition in critically ill infants and children / Enno D. Wildschut ... [et al.] -- Ethical issues in neonatal and pediatric clinical trials / Naomi Laventhal, Beth A. Tarini, and John Lantos.
"October 2012."
Includes bibliographical references and index.
Keywords: Pediatric pharmacology; Newborn infants -- Effect of drugs on; Child; Infant, Newborn; Infant; Drug Therapy